IDENTIFIKASI DAYA TAMPUNG BEBAN CEMARAN BOD SUNGAI DENGAN MODEL QUAL2E (STUDI KASUS SUNGAI GUNG, TEGAL – JAWA TENGAH) - Nugraha, Winardi Dwi; Cahyorini, Lintang (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Gung  River  is  a  one  of  the  river  in  Central  Java  which  pass  trough  Tegal  Region  with total length about 48 km. The important thing in environmental problems that faced by Gung River such as increasing the load of water pollution.  BOD is one of the water pollution indicator in the streams. To make easier in knowing the the amount of Total Maximum Dailly Load (TMDL)in Gung River , it  is identified TMDL  of BOD uses modeling principal with Qual2E Modelling. And than  it  is  compared  with    the standar  streams  due  to  PP  No.  82/2001  about  Water  Quality Management and  Water Pollution Control. The result of simulation due to TMDL uses minimum flow rate is compared with standard stream ini PP 82 / 2001. It indicate that the quality could not meet with the standard stream related with the class 1 and class 2. In Reach 1 ( km 1 – 3  ) could meet with standar stream of class 3 with TMDL 1,43 – 9,98 kg/day. All the stream along the river could meet with standar stream ini class 4 with TMDL of BOD is 7,13 – 865,34 kg / day. The  result  of  simulation  due  to  TMDL  uses  maximum    flow  rate  is compared  with  standard stream  ini  PP  82  /  2001.  It  indicate  that  the  quality  could  not  meet with the  standard  stream related with the  class 1 and class 2. In Reach 1 ( km 1 – 3  ) could meet with standar stream of class  3  with  TMDL  72.06  –  3134,51  kg/day.  All  the  stream  along  the  river could  meet  with standar stream ini class 4 with TMDL of BOD is 7277,82 – 10.340,27 kg / day.